Praktek Pembiayaan KPR Dengan Akad Ijarah Muntahiya Bittamlik (IMBT) Di PT. Bank Syariah Mandiri Cabang Bandung : Tantangan Dan Solusinya - Mulyana, Iwan (Banking & Management Review, 2022)
This study aims to identify and explain the practice of home ownership financing (KPR) with the Ijarah Muntahiya Bittamlik (IMBT) contract at PT. Bank Syariah Mandiri Branch Bandung. This research is descriptive qualitative in PT. Bank Syariah Mandiri Branch Bandung with interview techniques and documentation in collecting data. Data analysis techniques with interactive analysis models proposed by Miles and Huberman, among others; data collection, data presentation, data reduction and conclusions in the form of delineation and verification of home ownership credit (KPR) financing practices with the Ijarah Muntahiya Bittamlik (IMBT) contract at Bank Syariah Mandiri Branch Bandung. The results show that the practice of financing home ownership credit (KPR) with the Ijarah Muntahiya Bittamlik (IMBT) contract at Bank Syariah Mandiri, Bandung branch was still considered necessary to be optimized for future improvements by improving better services and education to the public. In addition, it also discloses the terms, benefits, mechanisms, factors that affect late installment payments as well as solutions offered by banks so that the financing program can provide benefits to customers and banks.